ANALISIS TRANSAKSI SYARIAH DI PASAR SYARIAH KAMPAR RIAU - Waldelmi, Idel; Putri, Dwika Lodia (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
This study discusses the analysis of Islamic transactions in the Islamic market ulul albab siak hulu kampar Riau. According to Athoillah and Waldelmi, I, the dimensions of buying and selling / sharia transactions for customers can be seen in the existence of goods, prices, honesty / trustworthiness, buying and selling systems and Aqad. This study uses a survey method on ulul albab sharia market customers, using questionnaires, discussions, interviews and analyzed with descriptive techniques, the results obtained from research that the implementation of sharia transactions conducted in the ulul albab sharia market in the assessment is quite appropriate. Using five dimensions and proven to be the highest dimension in the payment system done in cash, which means that almost all transactions carried out in the Islamic market by market customers are preferred with cash payments while the lowest dimensions are in the buying and selling system in the Islamic market where between ulul albab sharia market with an ordinary (conventional) market is the same in terms of carrying out buying and selling transactions Keywords: Sharia customers, traders and buying and selling systems